Healthy living of children of mothers who work in recycling: difficulties and possibilities - Mello, Giovana Batistella; Forgiarini, Amanda Ruiz; Bissacot, Carine Pelegrini; Adames, Nathália Hoffmann; Backes, Dirce Stein (Disciplinarum Scientia | Saúde, 2021)
Objective: To understand the meaning of healthy living and, in a second step, to expand the possibilities of healthy living for children of mothers who work in recycling, based on systematic interventions at an Association of Recyclable Materials. Methodology: This is a research-action, developed between August/2019 and December/2019, in an Association of Recyclable Materials, located at the central region of Rio Grande do Sul, through systematic interventions promoting health. Results: It was evidenced that mothers who work in recycling are unable to promote healthy living for their children due to overworking and low financial income, which interferes with early weaning and creates a fragile bond between mother and child. Final considerations: The interventions allowed the expansion of the possibilities of healthy living of children of mothers who work in recycling, considering the improvement of theoretical and practical themes and the social empowerment of the mothers.